FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA (Students' Journal of Accounting and Banking, 2014)
An enterprise value of investors perceptions of the company. Value of the company better reflects the state of a company, because the value indicates that the company has a good performance and a good internal control system. Value of the company is also an indicator for investors to invest their money into a company, so the company had to increase the value of the company to attract investors to provide capital.The purpose of this study was to analyze the effect of debt policy, profitability and firm age on firm value. The sample in this study manufacturing companies listed in Indonesia Stock Exchange in 2010-2012. The sampling technique used to determine the sample using purposive sampling is that sampling by specifying certain criteria. Regression analysis showed that the debt policy and firm age has no effect on firm value, while profitability has a positive effect on firm value.Keywords: Debt Policy, Profitability, Age Company, Corporate Value